Toponimi Wilayah di Kecamatan Lau Kabupaten Maros (Kajian Antropolinguistik) (BASASTRA: JURNAL KAJIAN BAHASA DAN SASTRA INDONESIA, 2025)
Toponymy serves as a bridge to explore and rediscover knowledge related to past history. This is because the exploration of the naming of a place cannot be separated from the historical background, events, stories, myths, culture, and figures that shaped the place, which can provide valuable lessons for the community. This study aims to examine the cultural meaning of regional naming in Lau sub-district, Maros Regency, using a qualitative descriptive approach. Data collection techniques used were interviews, observation, and documentation. Meanwhile, data analysis used the Miles and Huberman model of qualitative data analysis techniques, which included interview transcriptions, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the cultural meaning of regional naming in Lau sub-district is very diverse, including names formed from historical events and honoring important figures such as Lemo-lemo, Bonto Kadatto, Tamala'lang, Baru-Baru, Soreang, Marana, and Bonto Rea. Names derived from geographical references and natural characteristics, such asKa'ne-Ka'ne, Kalumpang, Bonto Manai, Balange, Bonto Maero, Bonto Cabu, Bonto Kadatto and so on, as well as names rooted in local culture and traditions, such as Macoa, Garonggong, Pemelakkang Jenne, Bonto Te'ne, Sampobia, and so on.